IMPROVING PRONUNCIATION ABILITY USING CARTOON FILMS IN SMPN 3 SUBAH - Reja Vilan Topi; Endang Susilawati; Luwandi Suhartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis thesis was conducted to describe on how cartoon films can improve students’ pronunciation ability and how cartoon films can improve students’ pronunciation ability in pronouncing correct word. The method used in this research was collaborative action research. The research was conducted in two cycles from July 16th until July 19th, 2019 at the eighth grade of SMP Negeri 3 Subah. The research data were collected by using techniques of observation, document, and test. The data were analyzed through a constant comparative method and descriptive statistics. The research findings and discussion show that the pronunciation of the students of VIII at SMPN 3 Subah improved through the use of cartoon film. The activities were conducting using PowerPoint presentations, recordings of learner’ production technique; reading aloud; listening and imitating. Those activities gave an improvement in the students’ pronunciation. The implementation of reading aloud could improve students’ pronunciation — the texts for reading aloud that given contained sentence stress. The students were helped to have excellent intonation when they read the text. The result of the research implies that English teachers need to choose the appropriate media in teaching pronunciation. The proper media to teach pronunciation is cartoon films.Keywords: Cartoon Film, Pronunciation, Word Stress.